2011
DOI: 10.1158/1078-0432.ccr-11-1664
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mTOR/4E-BP Pathway in Endometrial Cancer

Abstract: Endometrial cancer is the most common gynecologic malignancy. Although it is highly treatable in the early stages of disease, therapies for advanced and recurrent disease are rarely curative. A molecular and genetic understanding of endometrial cancer involves the mTOR signaling pathway, an emerging target for treatment of type I disease (the most common presentation). Endometrial cancers show a significant reliance on the mTOR pathway for survival, and studies to date have revealed a clinical advantage in tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…Understanding this relationship may become particularly important when targeting strategies are designed in the future. 37 We found an inverse relationship between TP53 'mutant'-like expression and loss of ARID1A expression in endometrial cancer and found no loss of ARID1A in non-endometrioid endometrial carcinomas. In ovarian cancer, TP53 mutations were found to be mutually exclusive with ARID1A mutations, 3 and in gastric cancer, a similar inverse relationship was identified.…”
Section: Modern Pathology (2013) 26 1525-1535mentioning
confidence: 62%
“…Understanding this relationship may become particularly important when targeting strategies are designed in the future. 37 We found an inverse relationship between TP53 'mutant'-like expression and loss of ARID1A expression in endometrial cancer and found no loss of ARID1A in non-endometrioid endometrial carcinomas. In ovarian cancer, TP53 mutations were found to be mutually exclusive with ARID1A mutations, 3 and in gastric cancer, a similar inverse relationship was identified.…”
Section: Modern Pathology (2013) 26 1525-1535mentioning
confidence: 62%
“…In contrast to nutrient starvation, cellular growth signals (along with nutrient opulence) such as receptor binding of IGF-1 suppress autophagy via the activation of Akt, which inhibits the TORC1 repressor TSC1/2 (in addition to a variety of other targets), resulting in the activation of TORC1. Active TORC1 inhibits the autophagy-relevant ULK1 complex ( Figure 2) and in parallel de-represses protein translation via inactivation of S6K and inhibition of the translational repressor translation initiation factor 4E-binding protein 1 (4E-BP1) (10).…”
Section: The Enemy Inside: Protein Acetylation Interferes With the Aumentioning
confidence: 99%
“…Advances in the understanding of the molecular pathology of endometrial carcinoma have lead to the development and testing of targeted therapies (12,13). Of the potential therapeutic targets identified to date, the mTOR signaling pathway is a major target for treatment of this disease (14). mTOR is a highly conserved Ser/Thr kinase that integrates diverse signals, including nutrients, growth factors, energy, and stresses to control cell growth, proliferation, survival, and metabolism (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%